ZCT 535/ 4 - Nuclear Medicine and Radiotherapy Physics [Perubatan Nuklear dan Fizik Radioterapi] - February - March 2005 - PPSF, Pusat Pengajian Sains Fizik (2005)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2004/2005 February - March 2005 ZCT 535/ 4 - Nuclear Medicine and Radiotherapy Physics [Perubatan Nuklear dan Fizik Radioterapi] Duration: 3 hours [Masa : 3 jam ]